Clincopathological characteristics and treatment outcomes of oral leukoplakia by carbon dioxide laser excision in the elderly patients. Issue 5 (13th January 2020) - Yang, Shih‐Wei; Lee, Yun‐Shien; Chang, Liang‐Che; Hwang, Cheng‐Cheng; Chen, Tai‐An
Abstract: Background: Older age is one of the factors associated with malignant transformation of oral leukoplakia (OL). The purpose of this study is to analyze the clincopathological features and treatment outcomes of OL in the elderly patients. Methods: The demographic data and histopathological results of the patients (age ≥ 65) who received carbon dioxide laser surgery for OL from 2002 to 2017 were analyzed statistically. Results: There were 53 males and 16 females, with a mean age 71.2 ± 4.9. The follow‐up time was 42.5 ± 35.2 months. In the univariate analysis, morphology, pathology, and area were found to be factors associated with postoperative recurrence. Among these factors, pathology and area were the independent predictive factors for recurrence in the multivariate logistic regression model. Malignant transformation occurred in 8 of 69 patients (11.6%). Conclusions: The pathological high‐risk dysplasia and area of OL were the two prognostic factors for postoperative recurrence.